Adalimumab for Crohn's disease: Long-term sustained benefit in a population-based cohort of 438 patients. (1st August 2014) - Peters, Charlotte P.; Eshuis, Emma J.; Toxopeüs, Florien M.; Hellemons, Merel E.; Jansen, Jeroen M.; D'Haens, Geert R.A.M.; Fockens, Paul; Stokkers, Pieter C.F.; Tuynman, Hans A.R.E.; van Bodegraven, Adriaan A.; Ponsioen, Cyriel Y.; ,
Abstract: Background and Aims: Adalimumab is an effective therapy for induction and maintenance of Crohn's disease. However, results in clinical trials don't necessarily reflect daily clinical practice. Therefore, we assessed real-life long-term clinical response to adalimumab in a large population-based cohort and identified clinical parameters affecting response Methods: All consecutive patients in North-Holland that started adalimumab between 2003 and 2011 were included, of which medical charts were reviewed. Response to induction therapy was assessed after 3 months. Sustained benefit of maintenance therapy was calculated from Kaplan–Meier survival tables depicting ongoing adalimumab treatment. Regression analyses were performed to identify factors predicting response to adalimumab therapy. Results: In total 438 Crohn's patients started adalimumab with 92.5% response to the induction phase. After 1 year 83.3% showed sustained benefit of maintenance treatment, followed by 74.0% after 2 years. Nevertheless, one third of patients were in steroid-free remission at the end of their follow-up. Response to induction was negatively affected by longer disease duration (OR 1.05; p < 0.01) and strictures (OR 3.73; p = 0.04). Increased CRP levels predicted higher rates of initial response (OR 0.31; p < 0.01). Concomitant thiopurines in the first 6 months of adalimumab treatment decreased the risk to fail maintenance therapy (HR 0.69, p = 0.05). Previous infliximab therapy did not affect response to adalimumab, however dose escalation was more often deemed necessary ( p < 0.01). Conclusion: Adalimumab was successful in the majority of patients, with 10% loss of response per subsequent year. Concomitant thiopurines might improve adalimumab maintenance treatment.